2011
DOI: 10.1007/s00586-011-2094-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of heterotopic ossification after cervical total disc arthroplasty: a meta-analysis

Abstract: Prognostic level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 34 publications
3
62
0
2
Order By: Relevance
“…This pooled prevalence increased to 16.7 % at 24 months. The pooled prevalence of any ossification was 44.6 % at 12 months and 58.2 % at 24-month [18]. In our study, 89.2 % of patients had an ossification Cgrade I at the 5-year follow-up.…”
Section: Pain Relief Medication Consumption and Quality Of Lifesupporting
confidence: 38%
See 1 more Smart Citation
“…This pooled prevalence increased to 16.7 % at 24 months. The pooled prevalence of any ossification was 44.6 % at 12 months and 58.2 % at 24-month [18]. In our study, 89.2 % of patients had an ossification Cgrade I at the 5-year follow-up.…”
Section: Pain Relief Medication Consumption and Quality Of Lifesupporting
confidence: 38%
“…Both combined make up 40.7 % of segments. A recent meta-analysis on heterotopic ossification by Chen et al [18] showed a pooled prevalence of 11.1 % of advanced HO at the 12-month follow-up. This pooled prevalence increased to 16.7 % at 24 months.…”
Section: Pain Relief Medication Consumption and Quality Of Lifementioning
confidence: 99%
“…More surgically related complications occurred in patients treated with fusion, largely from pseudarthrosis, dysphagia, graft donor site morbidity, and graft extrusion [1,13]. The most frequent complications of cervical disc arthroplasty included heterotopic ossification [6,22], implant wear, migration and subsidence [27], and segmental kyphosis [34]. Cervical disc arthroplasty could greatly reduce the risk of dysphagia compared with fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical advantage of cervical arthroplasty has been the maintenance of segmental mobility and, thereby, reduction or avoidance of adjacent-segment degeneration and other limitations of fusion [15,27,43]. The potential disadvantages are possible wear and toxicity [27], the issue of biocompatibility [41], high incidence of heterotopic ossification [6,22], and implant migration or subsidence [35].…”
Section: Introductionmentioning
confidence: 99%
“…2,7,16 Recently, a high prevalence of heterotopic bone formation has also been reported for patients who have undergone spinal total disc arthroplasty. 5,10,12,15,17,20 Heterotopic ossification can negatively affect patients' daily activity if it decreases mobility of the joints and implants. 16 The incidence and clinical significance of HO after implantation of ISP devices have yet to be clarified.…”
mentioning
confidence: 99%